Binding studies of ruthenium complexes with antithyroid drug - Dinosha, D S Berlin; Allen Gnana Raj, George; Sumitha Celin, Thangadurai (Acta Chimica Asiana, 2024)
Medicinal substances are essential to our daily existence. A prudent approach to metal complexation with already available medications may result in more stylish, intelligent, and effective drug compositions. Thus, the binding of [Ru(NN)3]2+ (NN = 2,2ˈ-bipyridine, 1,10-phenanthroline) with the antithyroid medication thyronorm has been studied in the current attempt. The use of absorption and emission spectrum techniques allowed researchers to examine the complexes' interactions with antithyroid medications. Studies of absorption and emission spectra show that the complex and medication interact through coordinated ligand hydrophobic and hydrogen bonding interactions.Analysis has also been done on the binding of the antithyroid medication Thyronorm to ruthenium complexes. The Benesi-Hildebrand plot was used to determine the binding constants of the drug complexes. Current research indicates that the Thyronorm pill has good affinity with [Ru(phen)3]2+complex.